How Does It Feel to Have One's Psychiatric Diagnosis Altered? Exploring Lived Experiences of Diagnostic Shifts in Adult Mental Healthcare - O'Connor, Cliodhna; Seery, Christina; Young, Claire (Frontiers in Psychiatry, 2022)
Background: Though the socio-emotional significance of psychiatric diagnoses and the frequency of transitions between diagnostic classifications are widely acknowledged, minimal research reveals how ‘diagnostic shifts’ are subjectively experienced by psychiatric service-users. Aim: This study investigated how adult service-users make sense of diagnostic shifts and their impacts on one’s life. Methods: Twenty-seven people with self-reported experience of diagnostic shifts opted into this qualitative study. Virtual narrative interviews invited participants to share their ‘diagnosis stories’. Interview transcripts were analysed using narrative thematic analysis to identify common and divergent experiences across participants. Results: Diverse experiences of diagnostic shifts were related: diagnostic shifts could both promote and undermine clinical trust, therapeutic engagement and self-understanding. The analysis suggested that shared and divergent experiences could be attributed to two dimensions of narratives: participants’ Interpretations of Diagnostic Shifts and Diagnosis-Specific Factors. Regarding the former, analysis produced a typology of three possible interpretations of diagnostic shifts, which were linked with consistently different antecedents, experiences and consequences. The latter dimension captured how experiences of diagnostic shifts also hinged on the unique meanings ascribed to the specific diagnoses gained and lost, particularly in relation to their perceived severity, stigma, personal associations, and related communities. Conclusions: Findings reveal how diagnostic shifts can be experienced as both traumatic and life-enhancing, depending on their social and subjective context. Understanding the range and predictors of variable experiences of diagnostic shifts is vital for sensitive clinical practice and communication.